Family type and accidents in preschool children. - Wadsworth, J (1983)
Children living in single-parent families or stepfamilies were found to be more likely to suffer accidental injuries in their first five years of life than children living with two natural parents. Frequent household moves, low maternal age, and perceived poor behaviour in the child were all more strongly associated with overall accident rates than family type, and these disadvantages were more common in atypical families. Family type appeared to be the most important influence on hospital admission after accidents. Overall, there was a close similarity in accident rates between children of single-parent families and stepfamilies, and both groups were more at risk than children living with both natural parents.